High-resolution mapping of architectural DNA binding protein facilitation of a DNA repression loop in Escherichia coli - Becker, Nicole A. (Proc Natl Acad Sci U S A, 2015)
Double-stranded DNA is a locally inflexible polymer that resists bending and twisting over hundreds of base pairs. Despite this, tight DNA bending is biologically important for DNA packaging in eukaryotic chromatin and tight DNA looping is important for gene repression in prokaryotes. We and others have previously shown that sequence nonspecific DNA kinking proteins, such as Escherichia coli heat unstable and Saccharomyces cerevisiae non-histone chromosomal protein 6A (Nhp6A), facilitate lac repressor (LacI) repression loops in E. coli. It has been unknown if this facilitation involves direct protein binding to the tightly bent DNA loop or an indirect effect promoting global negative supercoiling of DNA. Here we adapt two high-resolution in vivo protein-mapping techniques to demonstrate direct binding of the heterologous Nhp6A protein at a LacI repression loop in living E. coli cells.